Phytoremediation of Benzophenone and Bisphenol A by Glycosylation with Immobilized Plant Cells - Kei Shimoda; Hatsuyuki Hamada; Hiroki Hamada (SAGE Publishing, 2009)
Benzophenone and bisphenol A are environmental pollutions, which have been listed among "chemicals suspected of having endocrine disrupting effects" by the World Wildlife Fund, the National Institute of Environmental Health Sciences in the USA and the Japanese Environment Agency. The cultured cells of Nicotiana tabacum glycosylated benzophenone to three glycosides, 4-O-β-D-glucopyranosylbenzophenone (9%), diphenylmethyl β-D-glucopyranoside (14%), and diphenylmethyl 6-O-(β-D-glucopyranosyl)-β-D-glucopyranoside (12%) after 48 h incubation. On the other hand, incubation of benzophenone with immobilized cells of N. tabacum in sodium alginate gel gave products in higher yields, i.e. the yields of 4-O-β-D-glucopyranosylbenzophenone, diphenylmethyl β-D-glucopyranoside, and diphenylmethyl 6-O-(β-D-glucopyranosyl)-β-D-glucopyranoside were 15, 27, and 22%, respectively. Bisphenol A was converted into three glycosides, 2,2-bis(4-β-D-glucopyranosyloxyphenyl)propane (16%), 2-(4-β-D-glucopyranosyloxy-3-hydroxyphenyl)-2-(4-β-D-gluco- pyranosyloxyphenyl) propane (8%), and 2-(3-β-D-glucopyranosyloxy-4-hydroxyphenyl)-2-(4-β-D-glucopyranosyloxyphe nyl)propane (5%). Also the use of immobilized N. tabacum cells improved the yield of products; the glycosylation of bisphenol A with immobilized N. tabacum gave 2,2-bis(4-β-D-glucopyranosyloxyphenyl)propane (24%), 2-(4-β-D-gluco- pyranosyloxy-3-hydroxyphenyl)-2-(4-β-D-glucopyranosyloxyphenyl) propane (15%), and 2-(3-β-D-glucopyranosyloxy- 4-hydroxyphenyl)-2-(4-β-D-glucopyranosyloxyphenyl)propane (11%).